The impact of COVID-19 on the work routine of nursing professionals (Research, Society and Development, 2022)
At the end of 2019, there was the outbreak of COVID-19 in Wuhan, China, caused by the virus called by the International Taxonomy Committee (ICTV) as SARS-CoV-2, which spread rapidly throughout the world, with a high rate of transmissibility, through droplets of saliva, contaminated handshakes, sneezing and phlegm. Patients infected by the virus often need hospital care and, in this case, nursing professionals represent approximately 59% of the multidisciplinary team that works on the front line. These professionals have a fundamental role in inpatient care, as they provide the first assistance and accompany them until their discharge. Therefore, this study seeks to highlight the impact of the COVID-19 pandemic on the work routine of nursing professionals, which had many changes due to the need to deal with such a lethal pathogen and which demands such care in those infected. Descriptive research was carried out, with bibliographic source and qualitative approach, through bibliographic review, documentary research in official information systems. The analysis of the research was based on the bibliographic study, compiling the information and evaluating the way in which the findings served to analyze the theme. Eighteen articles were found in the LILACS and SciELO databases, according to which it was inferred that the main changes worked overload, lack of personal protective equipment, and, especially, mental illness in professionals.